The transformation of EU and NATO security narratives: towards resilience and total defence? - Bargués, Pol; Joseph, Jonathan; Juncos, Ana E (International Affairs, 2026)
Amid multiplying crises at the global level, the dominant narratives of the European Union and NATO have come under strain. Drawing on narrative approaches, we argue that the EU's previous dominant narrative of peace has been replaced by one of resilience. For NATO, resilience has worked to nuance the past dominant narratives of a military defence alliance and liberal security community. These narrative shifts have been catalysed by external shocks and the role of narrative entrepreneurs. This article finds evidence of increasing narrative convergence between the two main providers of European security. In a context of a deteriorating security environment, there has been a shift in the meaning of resilience from a transformational process (resilience as 'the ability to reform') towards a more inward-looking and defensive notion. Increasingly, a narrative supporting the goal of total defence through the strengthening of societal resilience is emerging within the EU and NATO.